Pengaruh Budaya dan Iklim Sekolah Terhadap Efektivitas Sekolah: The Influence of School Culture and Climate on School Effectiveness - Abdullah, Mohamad Syarief; Wan Mokhtar, Wan Khairul Aiman; Ma’ruf, Chasan (STAI Publisistik Thawalib Jakarta, 2024)
The aim of this research was to determine the influence of culture and school climate, either partially or simultaneously, on the effectiveness of State Elementary Schools in the Sukawangi District, Bekasi Regency. The research was conducted quantitatively with a correlational design. Data collection techniques involved questionnaires administered to a population and sample of 146 teachers. Data analysis included descriptive, linearity, and multicollinearity analyses. Hypothesis testing was conducted using F and t tests. The results of the study indicate that there is a significant influence of school culture on school effectiveness, followed by a significant influence of school climate on school effectiveness, and there is also a significant combined influence of school culture and climate on school performance effectiveness. Conclusion: effective schools are influenced by many aspects, one of which is the culture and climate of the school, which significantly affect school performance effectiveness.